2019
DOI: 10.5530/jyp.2019.11.47
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report on Linezolid and Cefuroxime Induced Leucocytoclastic Vasculitis

Abstract: A 65-year-old female diabetic patient with wet gangrene on left great toe developed skin eruptions and blebs over her limbs and lower abdomen after receiving three doses of tablet linezolid + cefuroxime (600mg+500 mg). The skin eruptions and blebs completely resolved fourteen days after discontinuation of tablet Linezolid + Cefuroxime. Based on her presentation (Skin eruptions and blebs), we consider that the condition was a result of linezolid+ cefuroxime administration. While the pathophysiology of these cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A total of 60 published articles were included, comprising a total of 74 cases published between 1955 and 2021 (Table 1). 20,26,27,30 86 Analyses of the reported cases of antibiotic-induced leukocytoclastic vasculitis revealed that it is associated with numerous classes of antibiotic, including penicillin (amoxicillin, amoxicillin-clavulanic acid, oxacillin), cephalosporins (cefazolin, cephalexin, cefuroxime, ceftriaxone, cefotaxime), fluoroquinolone (ciprofloxacin, levofloxacin, ofloxacin), macrolides (azithromycin, clarithromycin), vancomycin, teicoplanin, trimethoprim-sulfamethoxazole, dapsone, linezolid, pristinamycin, tigecycline, isoniazid, streptomycin, rifampin, ethambutol, and pyrazinamide.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 60 published articles were included, comprising a total of 74 cases published between 1955 and 2021 (Table 1). 20,26,27,30 86 Analyses of the reported cases of antibiotic-induced leukocytoclastic vasculitis revealed that it is associated with numerous classes of antibiotic, including penicillin (amoxicillin, amoxicillin-clavulanic acid, oxacillin), cephalosporins (cefazolin, cephalexin, cefuroxime, ceftriaxone, cefotaxime), fluoroquinolone (ciprofloxacin, levofloxacin, ofloxacin), macrolides (azithromycin, clarithromycin), vancomycin, teicoplanin, trimethoprim-sulfamethoxazole, dapsone, linezolid, pristinamycin, tigecycline, isoniazid, streptomycin, rifampin, ethambutol, and pyrazinamide.…”
Section: Discussionmentioning
confidence: 99%